PENGARUH KEDALAMAN DAN UMPAN BERBEDA TERHADAP HASIL TANGKAPAN LOBSTER (PANULIUS SP) DENGAN JARING LOBSTER (BOTTOM GILL NET MONOFILAMENT) DI PERAIRAN ARGOPENI KABUPATEN KEBUMEN - Kusuma, Rikza; -, Asriyanto; -, Sardiyatmo (Journal of Fisheries Resources Utilization Management and Technology, 2012)
Lobster net is Gill Net Monofilament which its operation system is blocking lobster movement. Thus, the lobsters are hooked and winded round onto net. In order to increase the amounts of lobster captured, it is necessary to use bait for collecting lobsters. This research has a purpose to find out is there any interaction between the disposition factor of grabbing tool in 5 and 7 meters depth and the usage of cow hide and goatskin to the amount of lobsters capture (Panulius sp) in Argopeni Kebumen Regency waters. This research uses experimental method. Experimental method is observation under made condition, where that condition is made by the researcher. This method is a methods object which is used to find out is there any cause effect relationship and how big that cause effect relationship. In 5 meters depth using goatskin bait, the amounts of lobster captured are 36. In 5 meters depth using cow hide bait, the amounts are 49. In 7 meters depth, the amounts of lobster captured are 25 by using goatskin bait and 33 by using cow hide bait. The result shows that the difference of grabbing tool disposition gives the effect to the amounts of lobster captured. The difference of bait also gives some effects to that amounts. The result shows that cow hide bait in 5 meters depth gets more lobsters than others.